The effect of Basel 3 on earnings management using loan loss provisions - Rosvold, Iselin (2018)
In this paper, I look at the effect of the implementation of Basel III on the practice of earnings smoothing using loan loss provisions in listed European banks. The aim is to contribute to a better understanding of how international regulation influence discretionary behavior, as well as considering if the Basel enhancements reduce aggressive income smoothing, as the activity can lead to consequences contrary to the regulation’s objectives. My main findings were statistically insignificant, however it indicated an effect of a reduced earnings smoothing activity using loan loss provisions in the three years after Basel III was implemented.